The EFL Teachers’ Perception Self-Directed Professional Development Toward Oral Language Maintenance - Aisyah, Miranda; Slamet Setiawan; Ali Mustofa (Loquen, 2023)
This case study presents an EFL teacher's perception of self-directed professional development aimed to maintain and enhance her oral language proficiency to support her professional growth. Semi-structured interviews were used as the primary guides to extract information concerning EFL teachers' self-directed professional development (PD) activities associated with the maintenance and enhancement of oral language proficiency. The participant of this study was an EFL teacher who experienced oral language attrition and has motivation to maintain her oral language proficiency. Data were analyzed descriptively to result in EFL teacher perceptions of self-directed PD activities that demonstrates a positive attitude towards improving and maintaining her oral language skills as an integral aspect of her professionalism. The result indicated that self-directed professional development activities had a significant impact on the participants' recognition of the importance of maintaining oral language skills. These activities also emphasized the need to continuously improve and enhance their oral language proficiency, highlighting the benefits it brings to both teaching and learning. One specific example mentioned was the participant's engagement in self-directed PD activities using Netflix series, which proved to be highly beneficial for improving linguistic features. These efforts contribute to her long-life growth as a language teacher, enabling her to provide effective language instruction and create an engaging learning environment for her students. The study highlights the importance of self-directed professional development in supporting EFL teachers' language maintenance and the positive impact it has on their professionalism.